Incidence and Mortality of Prostate Cancer in Commercial Airline Cockpit Crew: Systematic Review and Meta-Analysis - Hadia Khanani; George McClintock; Hilary Fernando; Gillian Heller; Rebecca Asher; Cindy Garcia; David P. Smith; Ian Getley; Nariman Ahmadi; Norbert Doeuk; Scott Leslie; Niruban Thanigasalam; et al. (Société Internationale d’Urologie Journal)
Commercial airline cockpit crew (CCC) are potentially exposed to occupational risk factors that may have detrimental health effects. However, available literature on prostate cancer (PCa) as a health outcome is conflicted. Therefore, this review of cohort studies aims to evaluate the incidence of and mortality from PCa in CCC based on studies published to date. PubMed, Medline, EMBASE and SCOPUS were searched from 1946 to April 2021. Cohort studies reporting standardized incidence ratios (SIR) and/or standardized mortality ratios (SMR) of PCa in CCC were included. Military, cabin crew and service personnel data were excluded. Independent data extraction was conducted, and study quality assessed. Standardized ratios were pooled using a fixed effects model and expressed with 95% confidence intervals. 75 studies were assessed for eligibility from which 6 involving 129 374 licensed CCC were included in the final analysis: Two reported incidence only, 1 incidence and mortality and 3 reported mortalities only. The pooled SIR for PCa in CCC was 1.41 (95% CI 1.17 to 1.71) with moderate heterogeneity (I2 = 53%) however, the pooled SMR was not statistically significant (1.08; 95% CI 0.94 to 1.24) also with moderate heterogeneity (I2 = 70%). The available evidence shows that CCC are at a higher risk of developing PCa but there is no evidence to suggest a similarly higher risk of death from the disease. The effect of early detection through PSA testing in this cohort is unclear. Occupational exposure to radiation and sleep disturbance may play a role, but clear evidence of additional risk is lacking. Our review indicates that most evidence is dated and to confidently assess contemporary health outcomes of CCC, further research is required.